2010
DOI: 10.1182/blood-2009-10-163329
|View full text |Cite
|
Sign up to set email alerts
|

How I treat elderly patients with myeloma

Abstract: The clinical approach to older patients with myeloma has to be modified to take into account comorbidities and the likelihood of higher treatment-related toxicity. Individualization of management and adequate supportive therapy are important to obtain the best response while minimizing adverse effects. Corticosteroids, novel agents, conventional cytotoxic agents, and high-dose chemotherapy with autotransplantation (modalities used in younger patients) are also used in older patients, although the elderly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…15,73 For patients with recurrent, severe bacterial infections, intravenous immune globulin can be effective. 65 Peripheral neuropathy (PNP) is an important toxicity of both thalidomide and bortezomib occurring in approximately 50% of patients. 74 PNP from thalidomide is cumulative, dose dependent and usually permanent.…”
Section: Management and Treatment Of Toxicitymentioning
confidence: 99%
“…15,73 For patients with recurrent, severe bacterial infections, intravenous immune globulin can be effective. 65 Peripheral neuropathy (PNP) is an important toxicity of both thalidomide and bortezomib occurring in approximately 50% of patients. 74 PNP from thalidomide is cumulative, dose dependent and usually permanent.…”
Section: Management and Treatment Of Toxicitymentioning
confidence: 99%
“…When compared with matched-pair patients treated with melphalan and prednison (MP), the efficacy of ASCT was significantly superior to MP in terms of complete response (CR) rate, event-free survival (EFS) and OS, without transplant-related deaths. Based on these reports, elderly patients with MM in otherwise fit medical condition have been considered to be eligible for ASCT irrespective of the chronological age in many institutions [21,22]. Accordingly, several single institution studies have reported their experience of ASCT in elderly patients [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…3 Disruption of HSC quiescence prematurely exhausts the HSC pool and causes hematologic failure under various stresses, such as oxidative, replicative, and metabolic, and DNA damage. 4 HSCs are exposed to various ROS, which are routinely generated during metabolic or inflammatory process (reviewed in Naka and Hirao 5 ). ROS induce a variety of responses in HSCs, including cellular proliferation and apoptosis.…”
Section: Comment On Yahata Et Al Page 2941mentioning
confidence: 99%
“…Indeed, mice with mutations in several oxidative stress response (Atm, Fancc, Fancd2, FoxO) and DNA damage repair (Lig4, Dna-pk, Ku80, Xpd, mTR) genes exhibit premature exhaustion of HSCs because of accumulation of ROS or DNA damage. 4,5,7 Less is known about how oxidative DNA damage affects the function and lifespan of human HSCs. Yahata and colleagues use a…”
Section: Comment On Yahata Et Al Page 2941mentioning
confidence: 99%
See 1 more Smart Citation